Sustainability of food side streams: a case study of fermented blends made with sour whey and sunflower press cake powder using the back-slopping technique - Mangieri, Nicola; Rosciano, Gerardo; Porcellato, Davide; Winther, Anja Ruud; De Noni, Ivano; Fracassetti, Daniela; Foschino, Roberto; Vigentini, Ileana (Frontiers in Sustainable Food Systems, 2023)
We investigated the possibility to manage a spontaneous fermentation of blends made with different proportions of two food side streams (bovine acid whey and sunflower press cake powder) through the application of a back-slopping technique, with refreshment steps of the mixed material incubated at 26°C in static conditions. A full-factorial 2-factors 3-levels Design of Experiment was applied to infer the effect of the percent (w/w) of press cake in the mixture (20, 25, 30%) and the rate of back-slopping inoculum (15, 30, 45%). pH value, titratable acidity, content of sugars, organic acids and phenolic acids, enumeration of Lactic Acid Bacteria, yeasts and moulds, bacterial contaminants, presumptive Bacillus cereus and Escherichia coli were measured for each fermentation step at 0 h, 24 h, 48 h and 72 h. On the same samples a metataxonomics analysis, targeted on bacterial 16S rRNA gene and fungal ITS region, was performed by using Illumina MiSeq platform. On average, good acidification (pH 4.61 ± 0.11; °SH/50 mL 28.17 ± 2.92) and high LAB counts (9.39 log CFU/g ± 0.25) were observed at the end of each refreshment. In all fermented mixtures B. cereus, E. coli and moulds counts were lower than the detection limit (< 2 log CFU/g), whereas bacterial contaminants, overall spore-formers, were always present (3.74 log CFU/g ± 0.27). After 72h the dropping of pH value was maximum, yielding significant differences compared to previous fermentation steps (p < 0.01); particularly, in the central points of DoE (25% of press cake and 30% of back slopping rate) the lowest pH (4.45 ± 0.06) was achieved. Results from both culture-dependent and -independent techniques were consistent: although Lactococcus lactis, continuously deriving from the acid whey, was the main LAB, Pediococcus pentosaceus appeared and, in some cases, became the dominant species. Finally, a long-term trial (about 1 month), using the best conditions previously pointed out, was performed with an extension of the incubation time to 84 hours for each refreshment. The increase of acidity forced the natural selection towards acid-tolerant microbial strains confirming the former results with positive outcome for a possible scaling up of the process.